2013
DOI: 10.1189/jlb.1012512
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage phenotypes during tissue repair

Abstract: Mp are crucial for tissue repair and regeneration but can also contribute to tissue damage and fibrosis. Mp can adopt a variety of functional phenotypes in response to different stimuli; two of the best-characterized in vitro phenotypes are a proinflammatory "M1" phenotype, produced by exposure to IFN-γ and TNF-α, and an anti-inflammatory "M2a" phenotype, produced by IL-4 or IL-13. M2a Mp are frequently termed "wound healing" Mp, as they express factors that are important for tissue repair. This review will su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
403
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 528 publications
(426 citation statements)
references
References 83 publications
10
403
1
1
Order By: Relevance
“…Of interest, similar findings have been reported in the mouse gut, where tissueresident macrophages exhibited an anti-inflammatory profile, both in the native state and during acute inflammation (42). However, macrophage polarization is not limited to the M1 and M2 states, but also includes regulatory and resolution-phase macrophages (43,44). Moreover, overlapping phenotypes and populations may exist simultaneously within the same tissue.…”
Section: Cd11bsupporting
confidence: 67%
“…Of interest, similar findings have been reported in the mouse gut, where tissueresident macrophages exhibited an anti-inflammatory profile, both in the native state and during acute inflammation (42). However, macrophage polarization is not limited to the M1 and M2 states, but also includes regulatory and resolution-phase macrophages (43,44). Moreover, overlapping phenotypes and populations may exist simultaneously within the same tissue.…”
Section: Cd11bsupporting
confidence: 67%
“…Using PBM at 660 nm (20 mW and 1.6 J) with the same experimental model, De Souza et al12 and Mesquita‐Ferrari et al16 also found a reduction in myonecrosis at 7 days as well as a reduction in TNF‐ α mRNA expression after 1 and 7 days. TNF‐ α is a proinflammatory cytokine that stimulates myogenic cell proliferation, but also inhibits its differentiation and fusion 3, 24. Therefore, the decrease in TNF‐ α expression during the experimental periods could explain the decrease in myonecrosis on Day 2 and the increase in immature muscle fibres on Day 7 in the group treated with PBM at 660 nm.…”
Section: Discussionmentioning
confidence: 99%
“…This is usually accompanied by a switch in macrophage henotype from proinflammatory M1 macrophages (classically activated) to anti-inflammatory/ prohealing M2 macrophages (alternatively activated). 92 Studies have shown that in slowly healing diabetic wounds, macrophages do not effectively remove apoptotic neutrophils 89 and the number of M1 macrophages outweigh the M2 macrophages. 93,94 This could contribute to the persistent inflammation observed in chronic, nonhealing wounds.…”
Section: Direct Effects Of Vegf On Keratinocytesmentioning
confidence: 99%